Comparison of reactions with different calcium sources for CaCO3 production using carbonic anhydrase. Issue 5 (20th June 2020) - Moon, Dea Hyun; Eu, Jun; Lee, Wonhee; Kim, Young Eun; Park, Ki Tae; Ko, You Na; Jeong, Soon Kwan; Youn, Min Hye
Abstract: In this study, we investigated the effect of calcium sources with different solubilities and the carbonic anhydrase (CA) enzyme on carbonate mineralization reaction, and analyzed the reaction rate, the morphology of the formed precipitate, and the surface. The CO2 mineralization rate was affected by the rate of CO2 hydration and the rate of Ca ionization. For all of the calcium sources tested, CA improved the overall carbonate mineralization rate, but depending on the solubility of each calcium source, the reaction rates were in the order of CaCl2 > Ca(OH)2 > CaO. From CaCl2, calcium carbonate was generated rapidly. This was due to the high concentration of calcium ions in the solution because it was easily dissolved. But because of its high surface energy, calcite and vaterite coexisted. On the other hand, Ca(OH)2 and CaO had relatively low solubility and the rate of calcium carbonate production was slow, but after the reaction, CaCO3 with a calcite structure was formed. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.